2000
DOI: 10.1093/clinchem/46.9.1351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Different Homogeneous Assays for LDL-Cholesterol in Lipoprotein-X-positive Serum

Abstract: Background: The purpose of this study was to evaluate the performance of two homogeneous assays for LDL-cholesterol (LDL-C), a polyethylene/cyclodextrin (PC) assay and a detergent (D) assay, which are based on different principles, in cholestatic serum. Methods: We compared serum LDL-C concentrations determined by the two assays for healthy normolipidemic subjects (n = 42) and cholestatic patients (n = 51). LDL-C concentrations obtained with the homogeneous assays were also compared with those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…The method has been extensively evaluated and compared with β-quantification and in multicenter evaluation (59), in samples of normolipidemic subjects (58,60,61), in patients with hyperlipidemia (58,(60)(61)(62), and in nonfasting samples (59,63). The method is not completely specific for LDL, since IDL is only partially recovered (64)(65)(66) and apoE-rich HDL and VLDL are not completely excluded (64)(65), the latter especially in diabetic patients (67), whereas results for Lp(a) are contradictory (58,66,68). It is also reported that small, dense LDL are partially recovered (66).…”
Section: Friedewald Equationmentioning
confidence: 99%
“…The method has been extensively evaluated and compared with β-quantification and in multicenter evaluation (59), in samples of normolipidemic subjects (58,60,61), in patients with hyperlipidemia (58,(60)(61)(62), and in nonfasting samples (59,63). The method is not completely specific for LDL, since IDL is only partially recovered (64)(65)(66) and apoE-rich HDL and VLDL are not completely excluded (64)(65), the latter especially in diabetic patients (67), whereas results for Lp(a) are contradictory (58,66,68). It is also reported that small, dense LDL are partially recovered (66).…”
Section: Friedewald Equationmentioning
confidence: 99%
“…Em consequência dessa diferença caracterizada, a decisão a respeito da conduta terapêutica pode ser inadequada, dependendo das metodologias e dos equipamentos utilizados. Estudos cujas publicações datam desde 1998 demonstram que considerável variabilidade analítica de LDL-C pode ser verificada em decorrência da utilização de metodologias baseadas em princípios analíticos distintos (5,9,8,28,31,33,38) .…”
Section: Discussionunclassified
“…5 Therefore accurate and precise measurements of subjects LDL-C concentrations are necessary to appropriately identify individuals with hypercholesterolemia and to monitor the response of various treatments as well as lifestyle changes. 6 The LDLs are spherical particles, having a hydrophobic oily core of cholesteryl ester and triglycerides (TG). These particles have a hydrophilic envelop of phospholipids, free cholesterol and apolipoproteins.…”
Section: Introductionmentioning
confidence: 99%